2021
DOI: 10.1016/j.intmar.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

This Way Up: The Effectiveness of Mobile Vertical Video Marketing

Abstract: The mobile environment of the 2020s is experiencing a vertical video revolution. The portrait, or vertical, screen format is replacing the traditional landscape, or horizontal, format to become the default for mobile video production and consumption. With the increasing use of vertical videos, an important, yet unanswered, question is how mobile users respond to this format. Therefore, we examine the effectiveness of mobile vertical versus horizontal video advertisements in terms of consumer interest, engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 63 publications
0
23
0
3
Order By: Relevance
“…Prior research has emphasized how gen z's love for social media and related isolation, as well as poor diet, are affecting their short-and long-term health (Priporas et al, 2022). In addition, previous studies about gen z's interaction with technology have also demonstrated their tech savviness and willingness to adopt new technologies (Romero & Lado, 2021) as well as how their interaction with mobile content leads to their engagement (Mulier et al, 2021). The current research began with an attempt to better understand why, how, and when gen z's perception of social isolation and social anxiety influences their online sharing of personal information.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has emphasized how gen z's love for social media and related isolation, as well as poor diet, are affecting their short-and long-term health (Priporas et al, 2022). In addition, previous studies about gen z's interaction with technology have also demonstrated their tech savviness and willingness to adopt new technologies (Romero & Lado, 2021) as well as how their interaction with mobile content leads to their engagement (Mulier et al, 2021). The current research began with an attempt to better understand why, how, and when gen z's perception of social isolation and social anxiety influences their online sharing of personal information.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Lana Mulier (2021) stated that the current mobile environment is undergoing a vertical video revolution. With three studies, it examined the efficacy of mobile vertical video advertising and horizontal video advertising in terms of consumer interest, engagement, and processing fluency, as well as the underlying mechanisms for efforts to watch video advertising on smartphones [4]. What's more, in AR marketing, mobile vertical video advertising increases customers' interest and engagement, and mobile users process vertical video advertising more smoothly than horizontal video advertising.…”
Section: Literature Review 21 the Concept Of Ar Marketing And Related...mentioning
confidence: 99%
“…Gyroscopes, multi-touch screens, and even 5G networks can offer more interaction possibilities for mobile devices ( Miao et al., 2021 ). Nowadays, mobile video marketing is widely regarded as the focus of enterprise strategy design ( Mulier et al., 2021 ). Mobile interactive video advertising is a type of media that has attracted wide attention.…”
Section: Literature Reviewmentioning
confidence: 99%